Compressive Strength of Recycled Green Concrete Affected by Chloride and Sulfate Exposures - Md Roknuzzaman; Md Rahman (Journal of Rehabilitation in Civil Engineering)
The use of recycled aggregate to make concrete is a viable option to minimize demolition waste load in landfills and to preserve the natural resources of aggregates. Several studies reveal the potential of recycled aggregates, which can be re-used in concrete, resulting in green concrete with acceptable strength parameters. However, the performance of green concrete under adverse exposure conditions is yet to be evaluated on a larger scale. The present study investigates the compressive strength of green concrete under chloride and sulfate exposure. C-20-grade concrete specimens are prepared using recycled coarse aggregates derived from demolished concrete blocks from an 8-year-old highway culvert. After 28 days of regular water curing, the specimens are subjected to chloride and sulfate environments by immersing them in chloride and sulfate solutions. Compressive strength tests are conducted after 28 days, 56 days, 84 days, and 112 days of immersion. The results are compared with normal concrete of the same composition. Green concrete is found to be more susceptible to salt attacks than regular concrete. Sulfate exposures happen to be more damaging compared to chloride exposures. A maximum of 36.73% loss of compressive strength is encountered for 112 days of immersion of specimen in 10%  solution. The study recommends that caution should be taken while using recycled concrete in chloride and sulfate-prone environments.